Two Gothic Mythological Heroes: Lilith and Al Karisi - Miyase Güzel (Şarkiyat Mecmuası)
Mythological knowledge dating back to primitive times contains the first human teachings about living and non-living beings. These teachings have survived to the present while changing in form. Mythology makes up the common mind maps of the history of humanity and in the most basic sense involves the thoughts that the first people produced in the process of making sense of the world in which they lived. Intertwined with nature, these people tried to make sense of the human and metaphysical worlds. These attempts are referred to as mythologies in folklore studies are a way of narrating by giving personalities to the beings in nature and to the experienced events. Mythologies have identities onto which mythologies reflect the social, political, cultural, and economic characteristics of the society to which they belong. In addition, mythologies develop through the belief and thought systems of the society in which they are produced. Through the advantages of their ancient pasts, Turkish and Jewish societies have deep-rooted mythologies, and the knowledge and experiences of these societies are reflected in their literature. Mythologies are a method for knowing the unknown and making sense of the incomprehensible and contain similar characteristics due to the collective consciousness. The Al Karısı [wife of Al] in Turkish mythology and Lilith in Jewish mythology are mythological heroes with similar physical and spiritual characteristics. These similarities are the result of the similar lives and imaginations of the two societies. The wife of Al and Lilith harm women and children and exhibit behaviors that disrupt societal order. In order for these societies to protect themselves from these two beings, people have developed a number of beliefs and practices for avoiding and/ or negotiating with them. This study is the result of a mythological evaluation centered on Lilith and the wife of Al and analyzes the similarities and differences between these two gothic characters who are frequently encountered in daily life and literary narratives in Turkish and Jewish mythologies.